Implementasi Kebijakan Program Keluarga Harapan di Kota Dumai - ANGRAINI, FITRI; Hasanah, Nurul; S.sos., M.Si, Erinaldi (Jurnal Administrasi Publik dan Bisnis, 2025)
The Family Hope Program (PKH) is a conditional cash transfer policy aimed at improving the welfare of poor households through access to basic education, health services, and social protection. This study aims to analyze the implementation of PKH in Dumai City by examining its execution process, supporting and inhibiting factors, and its impact on beneficiary household welfare. This research employed a literature study with a descriptive qualitative approach using secondary data obtained from official government documents, regulations, and relevant academic publications. The findings indicate that the implementation of PKH in Dumai City has been relatively successful, supported by non-cash transfer mechanisms and the role of social facilitators in ensuring program compliance. However, various challenges remain, including the limited number of facilitators compared to the number of beneficiaries, suboptimal accuracy of social welfare data, and low participation of beneficiary families in empowerment activities such as the Family Development Session (FDS). Communication issues between implementers and beneficiaries also contribute to the lack of understanding regarding the program’s objectives. This study highlights the importance of strengthening human resources, improving intersectoral coordination, and enhancing continuous socialization to ensure PKH achieves its long-term goals of empowerment and breaking the intergenerational cycle of poverty in Dumai City